2015
DOI: 10.1037/pag0000051
|View full text |Cite
|
Sign up to set email alerts
|

“Older is always better”: Age-related differences in vocabulary scores across 16 years.

Abstract: Cross-sectional studies of cognitive aging compare age groups at 1 time point. It is unclear from such studies whether age-related cognitive differences remain stable across time. We present a cross-sectional investigation of vocabulary scores of 2,000 younger and older adults collected across 16 years, using the same laboratory and protocol. We found a steady decrease with year of testing and an advantage for older adults. An additive relation between age group and year of testing implied that age-related dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
49
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 29 publications
12
49
0
Order By: Relevance
“…Studies reported that semantic processing remains stable in old age in language comprehension and production (Kavé and Mashal, 2012;Ramscar et al, 2014;Lacombe et al, 2015) since semantic process of language benefits from verbal knowledge (i.e., vocabulary and semantic memory) adults have acquired over years (Verhaeghen, 2003;Ben-David et al, 2015). Compared to young adults, older adults presented comparable performance in semantic processing tasks including semantic judgment (Little et al, 2004), semantic priming task (Gold et al, 2009), lexical decision task (Gold et al, 2009), and picture naming (Kavé and Mashal, 2012).…”
Section: Asymmetries Of Semantic and Phonological Retrieval In Old Agementioning
confidence: 99%
“…Studies reported that semantic processing remains stable in old age in language comprehension and production (Kavé and Mashal, 2012;Ramscar et al, 2014;Lacombe et al, 2015) since semantic process of language benefits from verbal knowledge (i.e., vocabulary and semantic memory) adults have acquired over years (Verhaeghen, 2003;Ben-David et al, 2015). Compared to young adults, older adults presented comparable performance in semantic processing tasks including semantic judgment (Little et al, 2004), semantic priming task (Gold et al, 2009), lexical decision task (Gold et al, 2009), and picture naming (Kavé and Mashal, 2012).…”
Section: Asymmetries Of Semantic and Phonological Retrieval In Old Agementioning
confidence: 99%
“…Since the late 1990s, there has been a growing interest in the cognitive and clinical psychology literature in the role of emotion processing in adaptive behaviours, including prosocial and productive social interactions (Kotz & Paulmann, 2011). The communication of emotions is a dynamic process and occurs through multiple dimensions including words (Ben-David, Erel, Goy, & Schneider, 2015) and non-verbal communication, such as that which is expressed in the tone of voice (Ben-David, Multani, Shakuf, Rudzicz, & Van Lieshout, 2016;Ben-David, Thayapararajah, & Van Lieshout, 2013;Ben-David, Van Lieshout, & Leszcz, 2011;Leshem, Arzouan, & Armony-Sivan, 2015). The ability to perceive emotions accurately and process them appropriately is crucial for effective social life (Schwartz & Pell, 2012).…”
Section: Emotion Processing In Adaptive and Maladaptive Behaviourmentioning
confidence: 99%
“…One of most notable cognitive skills improved with ageing (and not just preserved) is vocabulary (Ben‐David et al . ). Thus, using real words may somewhat alleviate the stress associated with the oral‐DDK task.…”
Section: Introductionmentioning
confidence: 97%